Better managed rangelands and more resilient pastoral systems through participatory rangeland management (PRM) in Tanzania - Flintan, Fiona E.; Sircely, Jason A. (International Livestock Research Institute, 2022)
A poster summary on better-managed rangelands and more resilient pastoral systems through participatory rangeland management (PRM) in Tanzania prepared by Fiona Flintan and Jason Sircely